2016
DOI: 10.1007/s00277-016-2864-y
|View full text |Cite
|
Sign up to set email alerts
|

The long-term outcome of reduced-intensity allogeneic stem cell transplantation from a matched related or unrelated donor, or haploidentical family donor in patients with leukemia: a retrospective analysis of data from the China RIC Cooperative Group

Abstract: This study compared 6-year follow-up data from patients undergoing reduced-intensity conditioning (RIC) transplantation with an HLA-matched related donor (MRD), an HLA-matched unrelated donor (MUD), or an HLA-haploidentical donor (HID) for leukemia. Four hundred and twenty-seven patients from the China RIC Cooperative Group were enrolled, including 301 in the MRD, 79 in the HID, and 47 in the MUD groups. The conditioning regimen involved fludarabine combined with anti-lymphocyte globulin and cyclophosphamide. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Select older patients (age > 50) with low HCT-CI (<= 2) and good performance status tolerated myeloablative haplo-HSCT with similar outcomes as younger adults [ 57 ]. Haplo-HSCT with a reduced-intensity regimen (RIC) with substitution of cyclophosphamide with fludarabine (Flu) was feasible in patients above 60 years of age, who exhibited similar engraftment and relapse rates as myeloablative conditioning in China [ 29 , 30 ]. Select adults ≥ 70 years with hematological malignancies are considered for transplant in the USA.…”
Section: Introductionmentioning
confidence: 99%
“…Select older patients (age > 50) with low HCT-CI (<= 2) and good performance status tolerated myeloablative haplo-HSCT with similar outcomes as younger adults [ 57 ]. Haplo-HSCT with a reduced-intensity regimen (RIC) with substitution of cyclophosphamide with fludarabine (Flu) was feasible in patients above 60 years of age, who exhibited similar engraftment and relapse rates as myeloablative conditioning in China [ 29 , 30 ]. Select adults ≥ 70 years with hematological malignancies are considered for transplant in the USA.…”
Section: Introductionmentioning
confidence: 99%
“…The cumulative incidence rates of II-IV GVHD and severe GVHD were 29.3% and 9%, respectively, it was no increase in incidence compared with literature. 2-year cumulative relapse rate (CR = 17.4%, NR+PR = 13.3%) and a 2- year TRM of 4.9% were maintained at a relatively low level compared with previously published literature on haploid transplantation [ 25 , 26 ]. The results showed that the recurrence was markedly reduced and the tolerance was good in haplo-HSCT.…”
Section: Discussionmentioning
confidence: 63%
“…First, the ex vivo depletion of T‐cells, which is accomplished using several techniques to reduce donor T‐cell counts in stem cell products, such as the selection of CD34+ cells, depletion of CD3+ and CD19+ cells, and depletion of αβTCR+ cells, is commonly performed in Europe 7–10 . Second, the GIAC protocol, which is based on a granulocyte colony‐stimulating factor to stimulate the donor's progenitor cell production, together with intensified immunosuppression (cyclosporine, mycophenolate mofetil, and short‐course methotrexate), anti‐thymocyte globulin to facilitate conditioning, and a combination of peripheral blood stem cell and bone marrow allografts, has been extensively used in China 11–13 . Lastly, in vivo depletion of alloreactive T cells, accomplished with high‐dose cyclophosphamide after unmanipulated stem cells were given to patients, was pioneered in the United States 14–16 …”
Section: Introductionmentioning
confidence: 99%